THE IMPACT OF HARD DRUG USE ON MARITAL INSTABILITY AND OUTCOMES IN NIGERIA: THE ROLE OF SOCIAL WORK INTERVENTIONS IN MITIGATING THE IMPACT - Ogungweru, Patience Obeunezi (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2024)
The negative impact of hard drug use on marriages and families is a persistent issue in Nigeria that is of great concern to policymakers and researchers alike. This paper examines the impact of hard drug use on marital instability and outcomes in Nigeria and the role of social work interventions in mitigating this impact. The paper finds that hard drug use has a detrimental effect on marriages and families, leading to financial instability, physical and mental health problems, and social isolation. In addition, several bottlenecks can complicate the work of social workers, including limited resources, stigma and discrimination. Despite these challenges, social work interventions can still be effective in helping individuals and families affected by hard drug use to improve their health and well-being. However, it is important to consider the limitations and challenges faced by social workers in implementing these interventions and to address them to ensure the best possible outcomes for those affected. Overall, the paper highlights the need for continued research and action on the issue of hard drug use and its impact on marriages and families in Nigeria.